Enzymatic antioxidants in tomatoes and sweet bell pepper fruits under abiotic factors - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Оlesia; Калитка, Валентина Василівна; Калитка, Валентина Васильевна; Kalytka, Valentyna (My University, 2014)
EN: Enzymatic antioxidants in tomatoes and sweet bell pepper fruits under abiotic factors.
Keywords: tomato; pepper; SOD; catalase; peroxidase